Rh(II)/Pd(0) Dual Catalysis: Carbenoid N-H Insertion/Allylation Cascade Reaction to Construct Highly Functionalized and Polysubstituted Pyrrolidines - Maocheng Tang; Xianyan Jiao; Deping He; Ji-Xing Zhao; Ping Liu; Chun-Tian Li (Molecules)
In the category of drugs approved by the U.S. FDA, pyrrolidine is the most frequently used core of five-membered nonaromatic heterocycles containing nitrogen. Herein, a Rh(II)/Pd(0) dual-catalyzed carbenoid N-H insertion/allylation cascade reaction has been developed. This protocol provide an efficient approach for the construction of diverse highly functionalized and polysubstituted pyrrolidines in high yields (up to 91%) with excellent chemoselectivities and high diastereoselectivities (>20:1) under mild reaction conditions.